Search
Ask a question

Answers by Philip P.

Ah, when you factor the -3 out of -15x-18, it becomes -3(5x+6).  Remember taking -3 out of -18, you get (-3)·(+6) = -18.

(2x2·x4)3   (2x2+4)3     {[Add exponents with the same base]   (2x6)3   23·(x6)3     [Cube both the 2 and the x6]   8x6·3        [Multiply exponents when you raise a power to...

College Algebra (answer)

Remember that y = f(x), so which ordered pair in f has an x = 2?  Answer: (2,3).  So f(2) = y = 3.   f(5) = 0   (ordered pair 5,0)) g(-2) = 0  (ordered pair (-2,0))   f(5) + g(-2) = 0 + 0 = 0   BTW, it's pi, not pie. ...

Help with limit (answer)

If you haven't gotten to L'Hopital's Rule yet, the numerator and denominator can be factored and simplified:        lim x→3 (x-3)2(x-7)/(x-3)2(x+2) = lim x→3 (x-7)/(x+2) = (3-7)/(3+2) = -4/5

Trig Question (answer)

sec2x - 1 = sec2x·sin2x   Now sec2x = 1/cos2x,  Substituting:        (1/cos2x) - 1 = sin2x/cos2x   Multiply both sides by cos2x:       1 - cos2x = sin2x     1 = cos2x + sin2x    Which...

logarithm help (answer)

32log3(5) = 3log3(5^2)      [Log Property: b·log(a) = log(ab)] = 3log3(25) = 25                [Log Identity: aloga(x) = x]

y = c + b·loga(x)   First, plug in (1,1) for the x and y values:        y = c + b·loga(x)      1 = c + b·loga(1)   Since loga(1) = 0 for any base, we get 1 = c.  Now plug in the second point, (5,7):       ...